PENGALAMAN PASIEN DIABETES MELITUS DALAM MENJAGA KADAR GULA DARAH AGAR TETAP TERKONTROL DI KP.SEGLOG RT.015 RW.05 - Iin Indriani; Kristina Everentia Ngasu (Nusantara Hasana Berdikari, 2021)
Diabetes mellitus is a chronic metabolic disorder caused by the pancreas unable to produce enough insulin or the body unable to use insulin effectively. The number of people with Diabetes Mellitus in the world is 387 million people with a prevalence of 8.3% of the population, every 7 seconds 1 person in the world dies of Diabetes Mellitus. The number of Diabetes Mellitus sufferers in Indonesia in 2017 was 10.3 million. The purpose of this study was to determine the experience of diabetes patients in maintaining blood sugar levels in order to keep them under control. The research method uses qualitative methods, with a descriptive phenomenological approach that aims to describe, explain, interpret and analyze the results in a deep and structured manner to obtain data about the patient's life experiences in the form of stories and narratives. The results of research on the experience of patients with diabetes mlitus in maintaining blood sugar levels so that the tta is controlled that has a variety of experiences. The conclusion of this research is diabetes mellitus is a metabolic disease because the body is unable to control the amount of glucose in the blood, the inability to control glucose levels in the blood occurs due to interference with the hormone insulin where the body is unable to produce enough or not at all, this causes hyperglycemia , where the state of high blood sugar is dangerous.